Effectiveness Test of Centella Asiatica Extract on Improvement of Collagen and Hydration in Female White Rat (Rattus Norwegicus Wistar) - Venesia, Nikko Fernando; Fachrial, Edy; Lister, I. Nyoman Ehrich (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
Gotu Cola (Centella asiatica) is one of the plants used as a skin care product because it contains triterpenoid, asiaticosida, madekakosida, flavonoids, which have antioxidant, anti-inflammatory properties and prevent premature aging. The purpose of this study was to compare the effectiveness of Centella asiatica extracts against increased levels of collagen and hydration in the skin of female white rats. This study is a non-experimental and experimental study, using a pre-test design post-test control group design. Non-experimental studies include the determination of gotu kola plants, extraction and manufacture of anti-aging cream preparations using gotu kola extract with concentrations of 2.5%, 5%, 7.5%, and 10%. Experimental studies include testing anti-aging activities. Data were analyzed by linear regression analysis. The results showed that the cream extract of C. asiatica 10% showed the highest increase in collagen levels by an average of 77.89% and an average hydration of 81.58%. Cream Centella asiatica 2.5% cream showed the lowest increase in collagen levels by an average of 21.12% and an average hydration of 39.40%. Concentration and time had a positive effect on collagen levels and hydration of female white rats. Conclusion: The administration of gotu kola herb extract cream increased the average collagen levels and skin hydration compared with controls. C. asiatica extract can be used as an alternative anti-aging agent in the science of dermato-cosmetology. Further research needs to be done using different measuring devices and also different parameters.